El humanismo en Sócrates y Platón. Una aproximación desde el siglo XXI - Varona Domínguez, Freddy (2017)
By means of Plato’s texts and texts of other authors, this paper characterizes humanism in Socrates’ and Plato’s philosophy, studies humanism as human prominence and as a fight against estrangement and for human improvement. Finally, it shows characteristics and roads of exposition: Education, love, State and poems.